2019
DOI: 10.5539/ass.v16n1p41
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Political Instability on Foreign Direct Investment in Lebanon

Abstract: Foreign direct investment (FDI) is an important determinant of economic growth. A wealth of literature has tackled its determinants; however few investigated the effect of political risk on FDI. Consequently, this study examines 12 ICRG political risk indicators, after removing multicollinearity and grouping them into three categories, to test the nature of this relation in the case of Lebanon over the period 2008-2018. The findings provide evidence of significant causality between all political risk factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
(11 reference statements)
0
6
0
1
Order By: Relevance
“…On the one hand, the simultaneous inclusion of all indicators leads to biased estimates as a result of multicollinearity; on the other hand, the inclusion of indicators in turn will increase the number of regressions in the study and can lead to difficulties when interpreting results. Therefore, in current research, the method of principal component analysis was implemented in order to structure the political stability indicators and obtain a sufficient amount of institutional indicators [53,54].…”
Section: Econometric Methodologymentioning
confidence: 99%
“…On the one hand, the simultaneous inclusion of all indicators leads to biased estimates as a result of multicollinearity; on the other hand, the inclusion of indicators in turn will increase the number of regressions in the study and can lead to difficulties when interpreting results. Therefore, in current research, the method of principal component analysis was implemented in order to structure the political stability indicators and obtain a sufficient amount of institutional indicators [53,54].…”
Section: Econometric Methodologymentioning
confidence: 99%
“…Studi selanjutnya juga mempertimbangkan implikasi risiko politik dan stabilitas politik pada arus masuk FDI. Misalnya, Bitar et al (2019) melakukan penelitian tentang dampak faktor-faktor tersebut untuk menarik FDI dalam perekonomian Lebanon. Para penulis kemudian menyimpulkan bahwa risiko politik secara signifikan mempengaruhi investasi asing langsung Negara berkembang yang mencari peningkatan investasi asing langsung dari negara maju, maka sangat penting bagi mereka untuk perlu meningkatkan lingkungan politik dan memberikan kondisi yang menguntungkan bagi negara investor (Groznykh et al, 2020).…”
Section: Hubungan Stabilitas Politik Dengan Fdiunclassified
“…Later studies also considered the implications of political risks and political stability on FDI inflows. For example, Bitar et al (2019) conducted a research on the impact of such factors for attracting FDI in the Lebanese economy. The authors then confirmed that political risk significantly affected foreign direct investment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It must be considered that all the indices employed in the research are strongly correlated. In order to deal with the multicollinearity problem, all these indicators were integrated into four groups (Bitar, 2019), which are depicted in table 2. Source: Authors Bearing the data and research results of previous studies in mind, the central hypothesis states that political risk indices have positive and significant impact on foreign direct investment, such that with an increase in the value of an index, the amount of foreign direct investment would increase.…”
Section: Datamentioning
confidence: 99%